(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Angiotensin II is a powerful growth stimulant that can lead to smooth muscle hyperplasia in vascular wall. Objectives: The present study was aimed to find out the anti-atherosclerotic effects of angiotensin II receptor blocker losartan. Methodology: This experimental animal study was carried out in the Laboratory of the Department of Pharmacology & Therapeutics at Banghabandhu Sheik Mujib Medical University (BSMMU) Dhaka from July 2008 to June 2009. Healthy Long-Evans Norwegian male rats aged between 3-4 months with an weight of 180 to 200 gm were randomly selected and were divided into 3 groups designated as group A, B and C. Group A was fed on standard rat diet; group B was fed soybean oil and group C was fed a 2% cholesterol enriched diet which was the suspension of cholesterol powder in soybean oil. After 8 weeks 10 rats of each group were sacrificed and remaining 20 rats of group C were continued to the part II of the experiment and divided into two groups known as group I which was cholesterol fed control group and group II which were losartan treated group. After 8 weeks all the rats of two groups were sacrificed. Blood from each rat was collected to measure the lipid profile and malondialdehyde (MDA) level within erythrocyte. The aorta was separated and intima-media ratio was measured by using Image-pro plus software. Results: Losartan induces a significant reduction in serum lipids (p<0.001) and in atherosclerotic lesion size (p<0.001). It also significantly reduces the oxidative stress by reduction of malondialdehyde (MDA) level (p<0.001). Conclusions: In a atherosclerosis rat model, losartan reduces the oxidative stress and the neointimal inflammation and this could due to direct inhibition of angiotensin II in the arterial wall. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20765 J Shaheed Suhrawardy Med Coll, 2013;5(2):99-102